Glue and preservative effects on the properties and durability of engineered bamboo boards - Alipon, Marina A.; Garcia, Carlos M.; Bondad, Elvina O. (2018)
The effect of glue and preservative treatments on the physico-mechanical properties and durability against bamboo-destroying insects, respectively, of engineered bamboo boards from kauayan-tinik (Bambusa blumeana J.A. & J.H. Schultes) and giant bamboo [Dendrocalamus asper (Schultes f.) Backer ex Heyne] were evaluated. Costs of glues to bind the bamboo slats and chemical treatments were computed. Six glue types were used: polyvinyl acetate (PVAc) for interior and exterior use (Glue 1); PVAc for interior use (Glue 2); urea formaldehyde (UF, Glue3); Glue 3 + 5% isocyanate (Glue 4); Glue 3 + 1.5% isocyanate (Glue 5); and phenol formaldehyde (PF) (Glue 6). The chemical used included: permethrin (T1); fenvalerate (T2); deltamethrin (T3); propiconazole (T4); deltamethrin + propiconazole (T5); and disodium octaborate tetrahydrate. (DOT, T6) Standard procedures were applied in evaluating the physical (relative density and moisture content) and mechanical (modulus of rupture, modulus of elasticity in static bending, hardness, and shear) properties of the bamboo boards. Engineered bamboo samples glued with PF and UF did not pass the US Formaldehyde Emission Limits (FEL) for composite wood products. However, both passed the FEL for composite wood products in Japan, although UF fell in the average limit category. Overall, the combination of PVAc + deltamethrin is highly recommended for high-end products such as housing components (floor tiles, balusters, windows, and doors). The UF + deltamethrin combination was also cost-effective. However, the strength properties of UF ? particularly shear which measures the bonding strength of glue ? was significantly lower than samples glued with PVAc. (Author's abstract)